Perancangan Program Komunikasi Pemasaran Umkm Pikyeum Menggunakan Metode Benchmarking - Dimas Reza Pamungkas; Husni Amani; Ima Normalia Kusmayanti (eProceedings of Engineering, 2019)
Abstrak Pikyeum (Keripik Peuyeum) merupakan usaha kecil yang bergerak dibidang kuliner sejak tahun 2016 dan terletak di Kab.Bandung – Jawa Barat. Pikyeum ingin memperluas area pemasaran dan meningkatkan penjualan, namun masih memiliki keterbatasan dalam biaya,SDM dan pengetahuan mengenai komunikasi pemasaranya. Sehingga, penelitian ini dilakukan untuk merancang program komunikasi pemasaran yang sesuai dan dapat diaplikasin oleh Pikyeum. Dalam perancangan komunikasi pemasaran. Penelitian ini menggunakan metode benchmarking dengan pendekatan menggunakan Analytical Hierarchy Process (AHP) terhadap produk benchmark partner. Dimana pengumpulan data melalui kuisoner dan wawancara. Kesimpulan yang didapatkan dari penilitan berupa rancangan program komunikasi pemasaran yang dapat diterapkan oleh Pikyeum. Diantaranya, dengan melakukan bebas biaya pengiriman, diskon dan buy one get one, memaksimalkan pengunaan instagram, menerapkan endorsement, membuat website, menggunakan e-marketplace, sering mengikuti bazar dan pameran, dan menjual produk melalui outlet. Kata Kunci: UMKM Pikyeum, bauran komunikasi pemasaran, benchmarking, Analytical Hierarchy Process. Abstract Pikyeum (Peuyeum Chips) is a small business engaged in the culinary field since 2016 and is located in Bandung Regency - West Java. Pikyeum wants to expand the marketing area and increase sales, but still has limitations in costs, HR and marketing knowledge about marketing. So, this research was conducted to design a marketing communication program that is suitable and applicable for Pikyeum. his study uses a benchmarking method with an Analytical Hierarchy Process (AHP) approach to benchmark partner products. Where is data collection through questionnaires and interviews. The conclusion obtained from the research is the design of a marketing communication program that can be implemented by Pikyeum. In designing marketing communications. This study used benchmarking method with an Analytical Hierarchy Process (AHP) approach to compare partner products or similar products that have been successful in the market through the marketing communication mix. This method was carried out to collect information from benchmark partner products through questionnaires and in-depth interviews. Among them, by doing free shipping, discounts and buy one get one, maximizing the use of Instagram, implementing endorsement, creating websites, using e-marketplaces, often participating in bazaars and exhibitions, and selling products through outlets. Keywords: UMKM Pikyeum, bauran komunikasi pemasaran, benchmarking, Analytical Hierarchy Process